1992
DOI: 10.1055/s-0038-1646347
|View full text |Cite
|
Sign up to set email alerts
|

The Residues AGDV of Recombinant γ Chains of Human Fibrinogen Must Be Carboxy-Terminal to Support Human Platelet Aggregation

Abstract: SummaryThe carboxy-terminus of the γ chain of fibrinogen contains a sequence which is believed to be one of the domains that interacts with glycoprotein (GP) IIb/IIIa to support platelet aggregation. A normal variant of fibrinogen exists in which the four carboxy-terminal amino acids are replaced by 20 amino acids. This variant, known as γ’, has been reported to bind less effectively to platelets. The purpose of the present study was to engineer novel proteins to determine what differences in amino acid sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
(46 reference statements)
3
32
0
Order By: Relevance
“…Studies with purified recombinant fibrinogen from transfected BHK cells showed that recombinant fibrinogen (a2p2y2) supported platelet aggregation, whereas the variant (cr2Dy'2) was defective in platelet aggregation [26]. In addition, studies using the recombinant fibrinogen y chain variants showed that the four C-terminal residues were required to support platelet aggregation [27]. In this study, the binding of recombinant ClfA and adherence of S. aurues cells occurs to a site present at the C-terminus of wild-type fibrinogen but not in fibrinogen variants defective in their interactions with platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with purified recombinant fibrinogen from transfected BHK cells showed that recombinant fibrinogen (a2p2y2) supported platelet aggregation, whereas the variant (cr2Dy'2) was defective in platelet aggregation [26]. In addition, studies using the recombinant fibrinogen y chain variants showed that the four C-terminal residues were required to support platelet aggregation [27]. In this study, the binding of recombinant ClfA and adherence of S. aurues cells occurs to a site present at the C-terminus of wild-type fibrinogen but not in fibrinogen variants defective in their interactions with platelets.…”
Section: Discussionmentioning
confidence: 99%
“…mitting multivalent binding interactions [39]. However, recent studies have demonstrated that the intact C-terminus of the fibrinogen y chain is critical for fibrinogen-dependent platelet aggregation [26,27,401. Since the C-terminus of the fibrinogen y chain contains the Clf33 binding site, this bacterial protein was assessed for its ability to interfere with fibrinogen-dependent platelet aggregation induced by ADP, and platelet adhesion to immobilized fibrinogen under shear conditions.…”
Section: Clf33 Binds To the C-terminus Of The Fibrinogen Y Chainmentioning
confidence: 99%
“…[39][40][41][42] Subsequent studies showed that the ␥Ј chain does not promote platelet aggregation because it lacks the binding site required for platelet adhesion, ␥A residues 408 to 411. [43][44][45][46] Recently, Lancellotti et al reported that the ␥Ј chain reduces thrombin-induced platelet aggregation through a combined mechanism. 47 They showed that the ␥Ј chain, either in fragment D or the synthetic ␥Ј peptide, hinders both thrombin binding to GpIb␣ and thrombin cleavage of PAR1 on platelets.…”
Section: Influence Of the ␥ Chain On Platelet Aggregationmentioning
confidence: 99%
“…The reaction was quenched by the addition of 100 l of 1 M Tris-HCl (pH 8.0), vortexed, and left at room temperature for 30 min. The fluoresceinated peptide was fractionated by reverse-phase chromatography on a DeltaPak C 18 Radial-Pak cartridge HPLC column connected to a Waters 486 multi-wavelength detector. The labeling procedure can yield three forms of fluoresceinated peptide with the probe attached to 1) the N-terminal amino group, 2) the amino group of the internal lysine residue, and 3) the amino groups in both positions.…”
Section: Analysis Of Fibrinogen-binding Activity Of Recombinant Proteinsmentioning
confidence: 99%